Model of Appropriate Online Teaching and Learning Process in the Situation of the Coronavirus Disease of Undergraduate Students in Chongqing, China. - Dai, Liping (วารสารรัฐศาสตร์รอบรู้และสหวิทยาการ, 2023)
This research aimed to study and develop a model for appropriate online teaching and learning management specifically tailored to the needs of students in Chongqing, China. Data analysis revealed general student agreement towards the proposed model for online teaching (= 3.48). This consensus was evident across all three stages of learning: pre-learning (=3.5024), during the study (=3.47), and evaluation (= 3.46). Critical practices and strategies were identified at each stage. In pre-learning, readiness checks (=3.46), determination of suitable teaching channels (= 3.52), and engaging lesson introductions (= 3.49) were favored. During the study phase, periodic comprehension checks (= 3.48), progressive learning techniques (=3.47), and fostering a collaborative online environment (=3.47) were appreciated. In the evaluation phase, continual instructor self-evaluation (=3.48), remedial assistance for low-performing students (=3.47), and scheduled comprehension tests (=3.46) were considered beneficial.